The mechanism of Danzikang Knee Granule in regulating the chondrogenic differentiation of mesenchymal stem cells based on TGF-β signaling pathway in cartilage repair in knee osteoarthritis - Xiaoyu, Yu; Hui, Xiong; Xiaolong, Lu; Lili, Xiang; Zhuo, Yang; Xinyu, Qi (Cellular and Molecular Biology, 2022)
This study aimed to explore the mechanism of Danzikang Knee Joint Granules in regulating the differentiation of mesenchymal stem cells into cartilage to cartilage repair of knee osteoarthritis based on the TGF-β signaling pathway. For this purpose, 60 SD rats were divided into four groups; the control group and treated groups with low, medium, and high concentrations of Danzikang. The histopathology of rats was analyzed and TGF-β signaling pathway-related proteins were determined. Results showed that the average optical density in serum of the Danzikang Granule intervention group was significantly higher than the control group (P<0.05), and the average optical density increased with drug concentration increasing (P<0.05). Compared with the control group, Danzikang knee granule cell survival in the intervention group was elevated the serum and reduced cell apoptosis rate (P < 0.05). Danzikang knee infusion concentrations were positively correlated with bone marrow mesenchymal stem cell survival rates (P < 0.05), and negatively correlated with apoptosis rate (P < 0.05). TGF-β1, BMP2, and BMP4 were significantly increased in the three concentrations of the Danzikang Granule serum intervention group (P<0.05). TGF-β1, BMP2 and BMP4 were significantly increased in the high concentration group, while TGF-β1, BMP2 and BMP4 were significantly decreased in the low concentration group (P<0.05). The Wakitani histological score of the control group was significantly lower than the other three groups (P<0.05). In general, Danzikang Knee Granule plays a role in cartilage repair in knee osteoarthritis by promoting mesenchymal stem cell proliferation and cartilage differentiation, and the specific mechanism may be related to TGF-β1/BMPs signaling pathway.